2015
DOI: 10.1038/nnano.2015.56
|View full text |Cite
|
Sign up to set email alerts
|

Gate-tunable memristive phenomena mediated by grain boundaries in single-layer MoS2

Abstract: Continued progress in high-speed computing depends on breakthroughs in both materials synthesis and device architectures. The performance of logic and memory can be enhanced significantly by introducing a memristor, a two-terminal device with internal resistance that depends on the history of the external bias voltage. State-of-the-art memristors, based on metal-insulator-metal (MIM) structures with insulating oxides, such as TiO₂, are limited by a lack of control over the filament formation and external contr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
589
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 613 publications
(607 citation statements)
references
References 35 publications
14
589
2
2
Order By: Relevance
“…As an interesting application involving GBs, a memristor was fabricated using MoS 2 , where the memristive behavior was ascribed to GB migration. [21] Concerning their characterization, grain boundaries are often visible as lines in photoluminescence or Raman images. [14] Alternatively, oxidation can be used to make the grain boundaries easier to distinguish under atomic force microscopy, scanning electron microscopy, or optical microscopy.…”
Section: Progress Reportmentioning
confidence: 99%
“…As an interesting application involving GBs, a memristor was fabricated using MoS 2 , where the memristive behavior was ascribed to GB migration. [21] Concerning their characterization, grain boundaries are often visible as lines in photoluminescence or Raman images. [14] Alternatively, oxidation can be used to make the grain boundaries easier to distinguish under atomic force microscopy, scanning electron microscopy, or optical microscopy.…”
Section: Progress Reportmentioning
confidence: 99%
“…Moreover, realization of possible new applications also benefits from the development of gate control, such as in the observation of gate-tunable memristive device. [7] Raman spectroscopy is a versatile probe in studying the crystalline and vibrational properties of TMDs. [8][9][10][11][12] Gatetunable phonon properties in graphene, [13,14] MoS 2 , [15] and black phosphorus [16] have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The abrupt change of the cantilever phase (fraction of phase shift >0.9, see Figure 3f) in the EFM images across a bisecting grain boundary (GB) in MoS 2 memory devices indicated that the electrostatic potential drops primarily at the grain boundary, i.e., the GB is resistive, consistently with the overall higher resistance of a bisecting-GB memristor compared to a bridge-GB memristor. Because the local surface potential and thus resistivity varies as a square root of the variation in the EFM phase signal, it was evaluated that more than 94% of the total device resistance would come from the grain boundary [18].…”
Section: Electrical Modesmentioning
confidence: 99%
“…Various memory devices have been fabricated with 2D materials, showing low power and energy consumption [16] as well as the possibility to be integrated in flexible devices [17]. Memristors based on grain boundaries in single layer MoS 2 devices have shown switching ratios up to~10 3 [18].…”
Section: Introductionmentioning
confidence: 99%